2007
DOI: 10.1016/j.ydbio.2006.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Periostin promotes atrioventricular mesenchyme matrix invasion and remodeling mediated by integrin signaling through Rho/PI 3-kinase

Abstract: Recent evidence suggests that extracellular matrix components may play a signaling role in embryonic valve development. We have previously identified the spatiotemporal expression patterns of periostin in developing valves, but its function during this process is largely unknown. To evaluate the functional role periostin plays during valvulogenesis, two separate three-dimensional culture assay systems, which model chick atrioventricular cushion development, were employed. These assays demonstrated that cushion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 58 publications
0
162
1
1
Order By: Relevance
“…Periostin is considered a matricellular protein with expression confined to cells in connective tissues, including the periodontal ligament, tendons, heart valves, myocardium, skin, and bone (6,7). Despite lacking an RGD domain, periostin is thought to interact with multiple integrins, including αVβ3, αVβ5, and α6β4, to initiate a variety of biologic effects including cell proliferation, cell migration, epithelial to mesenchymal transformation, modulation of the biomechanical properties of connective tissues, and regeneration of cardiac myocytes after injury (4,8,9). Periostin also binds type 1 collagen to promote fibrillogenesis (10), and periostin-null mice show aberrant type 1 collagen fibrillogenesis in skin and poor integrity of the periodontal ligament in response to mechanical stress (11,12).…”
Section: Mmp-9mentioning
confidence: 99%
“…Periostin is considered a matricellular protein with expression confined to cells in connective tissues, including the periodontal ligament, tendons, heart valves, myocardium, skin, and bone (6,7). Despite lacking an RGD domain, periostin is thought to interact with multiple integrins, including αVβ3, αVβ5, and α6β4, to initiate a variety of biologic effects including cell proliferation, cell migration, epithelial to mesenchymal transformation, modulation of the biomechanical properties of connective tissues, and regeneration of cardiac myocytes after injury (4,8,9). Periostin also binds type 1 collagen to promote fibrillogenesis (10), and periostin-null mice show aberrant type 1 collagen fibrillogenesis in skin and poor integrity of the periodontal ligament in response to mechanical stress (11,12).…”
Section: Mmp-9mentioning
confidence: 99%
“…During this period of peak PN secretion, the prevalvular ECM is progressively compacted and organized into specific layers or zones. Thereafter, when remodeling is completed, PN falls to baseline levels and does not increase again unless an injury occurs that promotes fibrosis (5,6).…”
Section: Periostin (Pn)mentioning
confidence: 99%
“…They concluded that periostin appeared to influence maturation and assembly of collagen I fibrils. This hypothesis is backed further from the observations that periostin null mice also appear to be unable to support normal valvular remodeling or maturation of the cardiac skeleton (Butcher et al 2007;Norris et al 2008b;Snider et al 2008). The hypothesis that periostin plays an important role in collagen fibrillogenesis has significant implications for connective tissue disease, where defects in collagen and elastin production result in chronic fibrotic conditions (Abraham et al 1982;Leask et al 2004;Uitto 1979;Uitto and Lichtenstein 1976).…”
Section: Periostin-ecm Interactions: Influence On Collagen Fibrillogementioning
confidence: 99%